1976
DOI: 10.1001/jama.236.4.365
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral ventricular enlargement. Chronic alcoholics examined by computerized tomography

Abstract: Computerized tomography was used to measure cerebral ventricular size in hospitalized alcoholic patients, all of whom had evidence of liver disease. Twelve alcoholic patients with neurologic symptoms such as withdrawal seizures, neuropathy, and drug overdose were included. All these patients had normal results from the mental status examinations by the time of discharge. Alcoholic patients had a much higher mean ventricular size compared to 60 control patients. One third of the alcoholics had markedly enlarged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
1
3

Year Published

1978
1978
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(27 citation statements)
references
References 6 publications
3
20
1
3
Order By: Relevance
“…Contrary to Avdaloff's (1978) report that all patients with alcohol withdrawal seizures have cortical atrophy in CT scan, our study shows that only 2 out of 10 patients with alcohol withdrawal seizures have similar CT scan findings. The incidence of cerebral atrophy in CT scan in this study (46%) is higher than that reported by Fox et al (1976) who observed 4 of 12 alcoholics (32%) with enlarged ventricles, but lower than that by Cala et al (1978) who found that cerebral atrophy was present in 19 of 26 alcoholics (73%) studied.…”
Section: Discussioncontrasting
confidence: 79%
“…Contrary to Avdaloff's (1978) report that all patients with alcohol withdrawal seizures have cortical atrophy in CT scan, our study shows that only 2 out of 10 patients with alcohol withdrawal seizures have similar CT scan findings. The incidence of cerebral atrophy in CT scan in this study (46%) is higher than that reported by Fox et al (1976) who observed 4 of 12 alcoholics (32%) with enlarged ventricles, but lower than that by Cala et al (1978) who found that cerebral atrophy was present in 19 of 26 alcoholics (73%) studied.…”
Section: Discussioncontrasting
confidence: 79%
“…Chronic alcoholism results in global brain atrophy with typical points of predilection for neurotoxic effects (16). Alcohol can also induce cortical and subcortical cerebral atrophy (15,16), atrophic changes in the cerebellum (17), enlargement of the cerebrospinal fluid space (15,18), and hippocampal volume loss (16,(19)(20)(21). Moreover, genetic factors (22), gender (23), age (24), amount of consumed ethanol, and the duration of alcohol consumption (25) may all affect the degree of alcohol-related brain damage.…”
Section: Introductionmentioning
confidence: 99%
“…Their finding initiated the search with neuroimaging tools for the location of brain tissue, assumed to have been lost in these patients. Other reports of enlarged ventricles or cortical sulci on magnetic resonance (MR) or CT images followed for other diagnoses, including Alzheimer's disease,2·3 chronic alcoholic abuse, 4 • 5 as well as for those infected with the human immunodeficiency virus (HIV). 6 • 7…”
mentioning
confidence: 99%